Algebraic models of application of computer systems and information technologies - Ovsyak, Volodymyr; Ovsyak, Oleksandr; Bui, Dmytro; Petruszka, Julia (2015 IEEE 13th International Scientific Conference on Informatics, 2015)
The mathematical models of diagrams of using cases of computer systems and information technologies (for Microsoft Visual Studio.NET platform) are built in the forms of Glushkov's algorithmic algebra systems, Zeitlin-Pogorilyi's modified algorithmic algebra systems, modified algorithmic algebras and primitive program algebras (PPA), which is an example of programing algebra class of composite type. Property of monotonicity and continuity is established for the branching operation of PPA as the corollary of the representation of branching operation in terms of set-theoretic constructions of function restriction over set using the properties of monotonicity and distributivity of function restriction and whole image of set with respect to binary relation.